Evaluation of disease chronicity by bone marrow fat fraction using sacroiliac joint magnetic resonance imaging in patients with spondyloarthritis: A retrospective study. (10th February 2019) - Koo, Bon San; Song, Yoonah; Shin, Ji Hui; Lee, Seunghun; Kim, Tae‐Hwan
Abstract: Aim: This study investigated the use of fat fraction (FF) measurements in the sacroiliac (SI) joint to determine radiologic progression in patients with spondyloarthritis (SpA). Method: A total of 138 patients who underwent pelvic magnetic resonance imaging (MRI) between September 2014 and March 2015 were retrospectively evaluated. The FF based upon fat deposition (%) using fat signaling on T1 and T2 weighted images in the sacroiliac joint was quantified using a 6‐echo variant of the modified Dixon technique. We defined the normal bone marrow as normal FF, bone marrow edema as active inflammatory FF, and fat metaplasia as post‐inflammatory FF. Results: The mean FF of normal marrow was 52.0% ± 10.4% and 50.5% ± 10.1% in the left and right SI joints, respectively. The mean FF of post‐inflammatory fat deposition was 81.9% ± 9.7% and 82.3% ± 9.6% in the left and right SI joints, respectively. The mean FF of active inflammatory fat deposition was 15.8% ± 5.9% and 13.5% ± 6.7% in the left and right SI joints, respectively. In multiple linear regression, post‐inflammatory FF was found to be significantly associated with radiologic progression, such as symptom duration, SI joint grade, and modified Stoke Ankylosing Spondylitis Spine Score. Conclusion: Post‐inflammatory FF indicates the chronicity of SpA. Evaluating FF using MRI in the SI joint will help to determine radiologic progression.